Anti-Aging Activity of Xylocarpus Granatum Phytoextracts and Xyloccensins K Compound - Syarif Maulana Yusuf; Rika Indri Astuti; Irmanida Batubara; Warinthorn Chavasiri (Universitas Gadjah Mada, 2021)
Cellular aging is promoted by the deleterious effect of free radicals. This can be lowered by antioxidant treatments. Xylocarpus granatum and its compound, Xyloccensins K have been reported to have antioxidant activity but there have been no reports of antioxidant and anti-aging activities at the cellular level. Thus, the aim of this study to investigate the antioxidant and anti-aging properties of X. granatum-derived extract and Xyloccensins K at a cellular level in yeast Schizosaccharomyces pombe. Four vegetative and three generative parts of X. granatum organs including root, stem, leaf, twig, seed, flesh of fruit, and peel of fruit were extracted using 70% ethanol by the maceration method. Whereas, Xyloccensins K was obtained from seed of X. granatum.  The samples tested, other than peel of fruit, prolonged cell longevity in lower concentration as compared to that without phytoextracts treatment. Also, our data indicate that all samples could promote oxidative stress tolerance phenotype, as yeast was capable of dealing with H2O2-induced oxidative stress treatment at 1, 2, and 3 mM H2O2 with the best phenotypes by the administration of twig extracts. Most of the phytoextracts showed an increase in mitochondrial activity, except that of seed extract. The result showed the administration of Xyloccensins K compound did not increase the expression of transcriptional factors of oxidative stress response gene cluster, sty1 and pap1. We suggest that the Xyloccensins K compound acts as direct Reactive Oxygen Species (ROS) scavenger. Thus further study in elucidating the phenomenon of longevity-induced X. granatum extract is required.